2014
DOI: 10.1042/bst20130270
|View full text |Cite
|
Sign up to set email alerts
|

Cavin-1: caveolae-dependent signalling and cardiovascular disease

Abstract: Supported by a project grant from the Chief Scientist Office [ETM/226] to TMP and a doctoral training studentship from the BBSRC Doctoral Training Programme in Biochemistry and Molecular at the University of Glasgow [BB/F016735/1] to JJLW.Keywords: Cavin-1, caveolae, inflammation, signal transduction, cyclic AMP Abbreviations: MCD: methyl-β-cyclodextrin, STAT: signal transducers and activators of transcription, SOCS: suppressor of cytokine signalling. 2 AbstractCaveolae are curved lipid raft regions rich in ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 47 publications
1
21
0
1
Order By: Relevance
“…Interestingly, the interaction of eNOS with caveolin1 was significantly increased 6 H after ex vivo storage. It has been earlier demonstrated that after nitric oxide synthesis, eNOS gets trapped into caveolae by the caveolin1 protein and this is a major mechanism that participates in termination of activity of eNOS . Overall, the results of this study provide evidence of a progressive endothelial injury of the liver vasculature during ex vivo storage.…”
Section: Discussionsupporting
confidence: 60%
“…Interestingly, the interaction of eNOS with caveolin1 was significantly increased 6 H after ex vivo storage. It has been earlier demonstrated that after nitric oxide synthesis, eNOS gets trapped into caveolae by the caveolin1 protein and this is a major mechanism that participates in termination of activity of eNOS . Overall, the results of this study provide evidence of a progressive endothelial injury of the liver vasculature during ex vivo storage.…”
Section: Discussionsupporting
confidence: 60%
“…In endothelial cells, caveolin-1 has complex roles in signaling due to its multiple functions. Translocation of enzymes like endothelial NO synthase into caveolae reduced their activity [ 34 ], whereas translocation of receptors and kinases into caveolae can lead to the formation of signaling hot spots [ 42 ]. Finally, caveolae-mediated uptake of receptors results in termination of signaling or facilitates intracellular signaling [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…The importance of endothelial cell membrane composition has been documented by several studies ( Table 2 ). The reason lies in the fact that endothelial cell membrane houses caveolae and lipid rafts where several receptors and signaling molecules crucial for cell function are concentrated [ 74 ]. Caveolae-associated receptor-mediated cellular signal transduction includes important pathways such as the nitric-oxide cGMP pathway, the NADPH oxidase and TNF- α –NF κ B induced cyclooxygenase-2 (COX-2) and prostaglandin E 2 (PGE 2 ) activation pathway [ 75 , 76 ].…”
Section: Influence Of N-3 Pufa On Endothelial Functionmentioning
confidence: 99%